2011
DOI: 10.1128/jb.05706-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Pasteurella multocida subsp. gallicida Anand1_poultry

Abstract: We report the finished and annotated genome sequence of Pasteurella multocida gallicida strain Anand1_poultry, which was isolated from the liver of a diseased adult female chicken. The strain causes a disease called “fowl cholera,” which is a contagious disease in birds. We compared it with the published genome sequence of Pasteurella multocida Pm70.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Comparison of available P. multocida sequences suggests that the presence of this region may be a defining feature of pathogenic avian-source P. multocida strains, as it was present in P1059, X73, and P. multocida subsp. gallicida strain Anand1 isolated from a chicken in India [47] but absent from strains Pm70, pathogenic bovine-source strain 36950 [48] and pathogenic swine source strains 3480 and HN06 [49]. Other studies have demonstrated an ability of avian-source P. multocida to ferment L-fucose, further suggesting that the majority of avian-source P. multocida strains harbor this system [9,33,50].…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of available P. multocida sequences suggests that the presence of this region may be a defining feature of pathogenic avian-source P. multocida strains, as it was present in P1059, X73, and P. multocida subsp. gallicida strain Anand1 isolated from a chicken in India [47] but absent from strains Pm70, pathogenic bovine-source strain 36950 [48] and pathogenic swine source strains 3480 and HN06 [49]. Other studies have demonstrated an ability of avian-source P. multocida to ferment L-fucose, further suggesting that the majority of avian-source P. multocida strains harbor this system [9,33,50].…”
Section: Resultsmentioning
confidence: 99%
“…For example, a P. multocida B: 2 strain can kill cattle and buffaloes at a low dose, but it has no effect on chickens, even at very high doses (Aktories et al, 2012 ). Isolates from non-avian hosts generally do not cause symptoms of fowl cholera in birds (Ahir et al, 2011 ; Peng et al, 2017 ). However, little is known about the genetic characteristics of P. multocida strains circulating in different hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, serotype A tends to have a wide host range ( 2 , 3 ). However strains isolated from non-avian hosts generally do not infect poultry, and the underling mechanisms are poorly understood ( 23 ). An avian P. multocida of serotype A, PmQ, isolated from tissues of a dead duck shows high virulence to poultry as well as to mammals.…”
Section: Discussionmentioning
confidence: 99%